Teachers’ Attitudes Towards English as Medium of Instruction - Khatri, Krishna Kumar (Journal of NELTA Gandaki, 2019)
English as medium of Instruction (EMI) has been a genuine issue of discussion in today’s pedagogical field among the concerned stakeholders including teachers. In this concern, a mixed method study entitled ‘Attitudes of teachers towards using English as Medium of Instruction (EMI) in Public Secondary Schools of Ilam was attempted to explore the teachers’ attitude towards using EMI in the public schools and challenges faced by them in course of adopting EMI. For this, twenty secondary level English teachers were accessed purposively and data were collected using questionnaire consisting of both close ended and open-ended questions. The results of the study revealed that teachers of public schools were found aware of the basic concept of the notion of English as a medium of instruction. They were found positive in implementing EMI in conducting their daily teaching and learning activities. The study also showed that teachers of secondary level have been facing different challenges in adopting EMI in the classroom like students’ weak exposure to English, mother tongue interference, unresourceful schools and linguistic diversity in the class. The study recommended that there should be conducive and encouraging environment in the public schools for the teachers for adopting EMI in the class. The schools should be made resourceful and well equipped with modern technologies. Moreover, the teachers should be made sound with pedagogically and professionally.